The Role of the Public Prosecutor as Dominus Litis in Filing a Demand for Acquittal (Comparison of the Old and The New KUHAP Criminal Procedure Code) - Endang Rahmawati AR; Megawati Barthos (Journal Customary Law, 2026)
The enactment of Law Number 20 of 2025 concerning the criminal procedure code marks a new milestone in the criminal justice system. It not only strengthens criminal justice as a whole but also has a significant impact on the role of the public prosecutor as dominus litis. The existence of the public prosecutor as dominus litis can be observed in one of their authorities, namely the power to bring cases before the court. Various legal literatures define dominus litis in different ways; however, it can be concluded that scholars generally agree that dominus litis refers to the role of the public prosecutor as the controller of the case. The implementation of the new criminal procedure code reinforces the status of the public prosecutor as the controller of the case, including granting the authority to submit an acquittal demand. This research employs a normative juridical method by linking statutory regulations to analyze legal norms related to the authority of the public prosecutor. In addition, this study utilizes various legal literatures as well as internal prosecutorial regulations to examine the implementation of the dominus litis principle in submitting acquittal charges. The results of the study indicate that the public prosecutor possesses full rights and authority in filing criminal charges, including acquittal charges, derived from the principle of dominus litis. This strengthened role is emphasized in the new criminal procedure code and its implementing regulations, where the public prosecutor functions not only to present indictments but also as the controller of the case who must prioritize objectivity based on facts revealed during trial. As the owner of the case, the public prosecutor bears full responsibility to ensure that the judicial process does not impose punishment on individuals who are not proven guilty. This underscores that the success of prosecution is not measured by the severity of punishment, but by the realization of justice and material truth in line with the spirit of reform in the national criminal procedure law.